Tetrathiomolybdate, a copper chelator inhibited imiquimod-induced skin inflammation in mice - Hsu, Peng-Yang; Yen, Hsu-Heng; Yang, Tao-Hsiang; Su, Che-Chun (Journal of dermatological science, 2018)
•Tetrathiomolybdate (TM) inhibited imiquimod-induced psoriasiform lesions in mice.•TM decreased cytokine levels in inflamed skin, splenocyte, and draining lymph node.•TM inhibited signals activation (Erk1/2 and STAT3) in keratinocyte and splenocyte. Copper is an essential metal for maintenance of many biological functions; however, excessive amount can induce inflammation and oxidative stress. Tetrathiomolybdate (TM) is a copper chelator for treatment of Wilson’s disease, and decreased the severity of autoimmune arthritis in mice. In this report, we evaluated the effects of TM in a mouse model for psoriasis. Imiquimod-induced psoriasis murine model was used. We applied immunohistochemistry staining and ELISA to determine levels of cytokines in the inflamed skin, splenocytes, and draining lymph nodes. In addition, we used keratinocytes and splenocytes to test the inhibitory effects of TM on cytokine production and activation of transcription factors. Our results showed that TM significantly reduced cumulative scores, epidermis thickness, and ki-67 expression in the inflamed skin. In addition, TM decreased skin cytokine levels and systemic inflammation. Moreover, TM suppressed activation in keratinocytes and splenocytes with reduction in phosphorylation of Erk1/2 and STAT3. These findings are strong evidence that TM can inhibit psoriasis in the model.